2021
DOI: 10.20473/jre.v6i1.28225
|View full text |Cite
|
Sign up to set email alerts
|

Deteksi Kadar Transforming Growth Factor (Tgf-Β) Pada Luka Akut

Abstract: Latar Belakang. TGF-β merupakan growth factor yang paling dominan dalam peningkatan sintesis kolagen, memiliki peran utama pada penyembuhan luka dengan menstimulasi fibroblas sehingga menimbulkan penyembuhan dan berperan serta dalam pembentukan parut, baik itu parut normal maupun abnormal seperti parut hipertrofik dan keloid. Penelitian ini bertujuan untuk mengukur kadar TGF-β pada fase penyembuhan luka.Metode. Penelitian eksperimental ini menggunakan randomized post test only control group design. Dua belas l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…In this study the concentration of TGF-β tended to decrease on H-14 compared to D-7. These results are different from the report of Wulandari et al [29], who reported that there was an increase in TGF-β on H-21 compared to H-5 in acutely injured rats. Oskeritzian [30], stated that an increase in TGF-β causes the activation of fibroblast proliferation which is necessary for collagen synthesis.…”
Section: Groupscontrasting
confidence: 99%
“…In this study the concentration of TGF-β tended to decrease on H-14 compared to D-7. These results are different from the report of Wulandari et al [29], who reported that there was an increase in TGF-β on H-21 compared to H-5 in acutely injured rats. Oskeritzian [30], stated that an increase in TGF-β causes the activation of fibroblast proliferation which is necessary for collagen synthesis.…”
Section: Groupscontrasting
confidence: 99%
“…36 TGF-β is a growth factor that plays a key role in wound healing by stimulating fibroblasts and is predominantly involved in increasing collagen synthesis. 37 In vivo studies have shown that curcumin mediates the infiltration of fibroblasts into the wound site, which naturally differentiates into myofibroblasts during granulation tissue formation. Treatment with curcumin also promotes the differentiation of fibroblasts into myofibroblasts, marking the initiation of wound contraction.…”
Section: Discussionmentioning
confidence: 99%
“…(Susetyowati et al, 2010). Gizi terutama kandungan kolagen meningkatkan penyembuhan luka (Wulandari et al, 2021). Faktor penghambat penyembuhan luka perlu dikendalikan, diantaranya faktor penghambatnya adalah diabetes melitus, sehingga edukasi diabetes melitus diharapkan dapat mengendalikan kadar glukosa darah (Lede et al, 2018).…”
Section: Metodeunclassified